Dilemma with leakage after sleeve gastrectomy - Mohammed Abbas; Abdelhafez Seleem (Wolters Kluwer Medknow Publications, 2018)
Objective The aim of this study was to evaluate methods of diagnosis and management of leakage after sleeve gastrectomy to decrease morbidity and mortality of this complication. Background Leakage is the commonest and most feared early complication in bariatric procedures. Leakage can occur from any site of staple line. Incidence of leakage after sleeve gastrectomy is in the range of 1-3%. Risk factors for leaks and complications were increasing weight, male sex, multiple comorbidities, previous abdominal procedures, or revisional surgery. Tachycardia with a heart rate in excess of 120 beats per minute was a good indicator of leakage. Patients and methods The study was conducted on 12 cases that had leakage after sleeve gastrectomy, where four cases were diagnosed early and were managed by re-exploration and repair of the site of leakage with feeding jejunostomy and eight cases were diagnosed late and managed as follows: five cases by gastric stent and pigtail for drainage of collection, two cases by exploration, and one case by pigtail insertion and conservative treatment. Results In this study, four cases experienced mortality owing to delay in diagnosis and septicemia. Two cases develop gastropleural fistula. There was long hospital stay. Two cases developed incisional hernia, and one case developed deep venous thrombosis (DVT). Conclusion Management of leakage in bariatric procedures requires early diagnosis and precise decision making tailored according to every case.